First genome‐wide analysis of the endangered, endemic lichen Cetradonia linearis reveals isolation by distance and strong population structure. Issue 9 (29th August 2018) - Allen, Jessica L.; McKenzie, Sean K.; Sleith, Robin S.; Alter, S. Elizabeth
Abstract : Premise of the Study: Lichenized fungi are evolutionarily diverse and ecologically important, but little is known about the processes that drive their diversification and genetic differentiation. Distributions are often assumed to be wholly shaped by ecological requirements rather than dispersal limitations. Furthermore, although asexual and sexual reproductive structures are observable, the lack of information about recombination rates makes inferences about reproductive strategies difficult. We investigated the population genomics of Cetradonia linearis, a federally endangered lichen in the southern Appalachians of eastern North America, to test the relative contributions of environmental and geographic distance in shaping genetic structure, and to characterize the mating system and genome‐wide recombination. Methods: Whole‐genome shotgun sequencing was conducted to generate data for 32 individuals of C. linearis . A reference genome was assembled, and reads from all samples were aligned to generate a set of single‐nucleotide polymorphisms for further analyses. Key Results: We found evidence for low rates of recombination and for isolation by distance, but not for isolation by environment. The species is putatively unisexual, given that only one mating‐type locus was found. Hindcast species distribution models and the distribution of genetic diversity support C. linearis having a larger range during the Last Glacial Maximum in the southern portion of its current extent. Conclusions: Our findings contribute to the understanding of factors that shape genetic diversity in C. linearis and in fungi more broadly. Because all populations are highly genetically differentiated, the extirpation of any population would mean the loss of unique genetic diversity; therefore, our results support the continued conservation of this species.